A closer look at urban development under the emergence of autonomous vehicles: Traffic, land use and air quality impacts. (June 2021) - Nadafianshahamabadi, Razieh; Tayarani, Mohammad; Rowangould, Gregory
Abstract: Autonomous vehicles (AVs) hold great promise for increasing the capacity of existing roadways and intersections, providing more mobility to a wider range of people, and are likely to reduce vehicle crashes. However, AVs are also likely to increase travel demand which could diminish the potential for AVs to reduce congestion and cause emissions of greenhouse gases (GHG) and other air pollutants to increase. Therefore, understanding how AVs will affect travel demand is critical to understanding their potential benefits and impacts. We evaluate how adoption of AVs affects travel demand, congestion and vehicle emissions over several decades using an integrated travel demand, land-use and air quality modeling framework for the Albuquerque, New Mexico metropolitan area. We find that AVs are likely to increase demand and GHG emissions as development patterns shift to the region's periphery and trips become longer. Congestion declines along most roadways as expanded capacity from more efficient AV operation outpaces increasing demand. Most of the population can also expect a reduction in exposure to toxic vehicle emissions. Some locations will experience an increase in air pollution exposure and traffic congestion from changes in land-use and traffic patterns caused by the adoption of AVs. Highlights: AVs evaluated with integrated travel demand, land use and air quality modeling. AVs result in more development at urban fringe and longer trip distances. Vehicle miles traveled and greenhouse gas emissions increase with AVs. Exposure to PM2.5 emissions decreases for most people in the study area. Congestion decreases along most, but not all, roadways.